2012
DOI: 10.1108/14720701211234564
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and corporate governance in Malaysian government‐linked companies

Abstract: This study examines the impacts of ESG on the corporate performance government-linked companies (GLCs) in Malaysia. For the period 2006-2012, ESG disclosure data were extracted from the Sustainalytics ESG performance reports, while financial data were obtained from the Bloomberg database. Data development analysis (DEA) was used to estimate efficiency in the first stage; a regression analysis was performed to test the relationship between ESG and efficiency in the second stage. The empirical results of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
208
3
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(277 citation statements)
references
References 49 publications
39
208
3
5
Order By: Relevance
“…According to Abd Rahman et al (2011), high gap between the minimum and maximum values on profitability ratio indicating that certain companies are enjoying a good financial performance while some are not and their study found that profitability do not have any relationship with the level of CSR disclosure among Malaysian GLCs. Esa and Mohd Ghazali (2012) also found that there is no relationship between profitability and CSR disclosure. Pressure to disclose CSR is more influenced by ''public'' rather than ''economic'' pressure (Esa & Mohd Ghazali, 2012).…”
Section: Profitabilitymentioning
confidence: 92%
See 3 more Smart Citations
“…According to Abd Rahman et al (2011), high gap between the minimum and maximum values on profitability ratio indicating that certain companies are enjoying a good financial performance while some are not and their study found that profitability do not have any relationship with the level of CSR disclosure among Malaysian GLCs. Esa and Mohd Ghazali (2012) also found that there is no relationship between profitability and CSR disclosure. Pressure to disclose CSR is more influenced by ''public'' rather than ''economic'' pressure (Esa & Mohd Ghazali, 2012).…”
Section: Profitabilitymentioning
confidence: 92%
“…Esa and Mohd Ghazali (2012) also found that there is no relationship between profitability and CSR disclosure. Pressure to disclose CSR is more influenced by ''public'' rather than ''economic'' pressure (Esa & Mohd Ghazali, 2012). Said et al (2009) on the other hand found that there is a significant positive relationship between profitability and the extent of CSR disclosure in Malaysian non-financial companies.…”
Section: Profitabilitymentioning
confidence: 92%
See 2 more Smart Citations
“…Their result had shown that different rhetoric is applied in companies' report where ethos had been the most common ethical perspective expressed in the report. † In Malaysia, the CSR study focuses on the nature, status or trend, quality, quantity and factors of disclosure in both Non-Shari'ah -compliant and the Shari'ah compliant companies' annual reports (Anuar et.al., 2004, Yahya et al, 2005, Amran and Devi,2008Said et al, 2009;Mohamad et al, 2010 ;Esa and Ghazali., 2012). However, none has been noted to have discussed the type of ethical categories and moral attitude of company in divulging CSR in the annual report.…”
Section: Introductionmentioning
confidence: 99%